2013
DOI: 10.1108/et-08-2012-0082
|View full text |Cite
|
Sign up to set email alerts
|

Creating future leaders: an examination of youth leadership development in Australia

Abstract: Purpose -In light of the research-practice gap in youth leadership development, the purpose of this paper is to examine the effectiveness of youth leadership development in Australia, on the basis of a multidimensional and holistic framework of servant leadership. Design/methodology/approach -In total, three separate studies were conducted to achieve the above purpose, namely 33 interviews with student leaders; ten interviews with secondary college teachers and principals, as well as youth leadership facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 48 publications
0
37
0
2
Order By: Relevance
“…Moreover, inductive analysis is used as the data analysis technique in this research, in this research, the data analysis was done together with the process of collecting data, not after the collecting data has finished. It was beneficial in term of meeting the complete finding, so that the collecting data still can be done if there was a shortage of the data [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inductive analysis is used as the data analysis technique in this research, in this research, the data analysis was done together with the process of collecting data, not after the collecting data has finished. It was beneficial in term of meeting the complete finding, so that the collecting data still can be done if there was a shortage of the data [7].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, a research from Eva & Sendjaya revealed that the teenager didn't get much on the training regarding to the ethics of the work. They still need to be trained on how to be a great leader, so that the able to run the office, the organization, or even the country well [7]. Teenagers also hold the greatest ability among other group of society on learning the new technology, such as internet.…”
Section: Teenager As Future Labormentioning
confidence: 99%
“…Youth Leadership Development. Adolescents understand the need for effective leadership and have the capacity to learn to be leaders (Anderson & Kim, 2009;Daugherty & Williams, 1997;Eva & Sendjaya, 2013). During the adolescent years, leadership training takes on many forms: service to others, participation in athletics and/or other co-curricular organizations, church groups, community programs, and potentially fundraising (Anderson & Kim, 2009), while other programs are more structured and based on an actual leadership curriculum (Daugherty & Williams, 1997;Kress, 2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Schools and community programming efforts provide many opportunities for adolescents to develop and learn leadership both in and out of a classroom setting (Eva & Sendjaya, 2013;Ricketts & Rudd, 2002). Eccles, Barber, Stone, and Hunt (2003) showcased after-school programs as means to promote continued school-based engagement, to curb social/ethnic inequalities in accomplishment, to prepare students for a skill-based work force, and to help decrease the amount of unsupervised time.…”
Section: Introductionmentioning
confidence: 99%
“…And thus, any business attempt to maximize profit should be accompanied by a considerable concern for achieving the well-being of the environment that the firm operates in, the welfare of internal and external stakeholders the firm serves and the wisdom the firm employs when dealing with its staff (Hymavathi et al, 2015). This creates a space for what academicians choose to label "responsible leadership" which urges organizations' leaders to maintain a noticeable commitment towards alleviating poverty, supporting peace, promoting freedom and safeguarding human rights in the communities their organizations serve (Bonoli, 2005, Carrasco, Earley (1989) and Eva & Sendjaya (2013) indicate that responsible leaders constantly disseminate the values of virtue, wisdom, empathy and sympathy for the betterment of their societies (Holt, 2006, Maak & Pless, 2008, Morland, 2015. That's why, the studies of (Fishbein & Ajzen, 1975, Pless, 2007, Maak& Pless, 2009, Pless & Maak, 2011, Nonet et al, 2016 elaborates that social responsibility is the main challenge facing responsible leaders nowadays.…”
Section: Introductionmentioning
confidence: 99%